The Switching Decision: Are Members of Superannuation Funds Rational and Informed Investors? - Sarath Delpachitra; Schumann Rafizadeh (Australasian Accounting, Business and Finance Journal, 2014)
The recent Cooper Review (Cooper 2010) attempted to address governance, structure, efficiency and operational problems by recommending changes without pinpointing the root causes and systematic design flaws of the Australian Superannuation System. Despite overwhelming evidence that members’ disengagement was a root cause of the problems, little attention was paid to the motivation and background of members to facilitate participation and decision-making. For instance, a very small percentage of members take their role in the superannuation industry seriously. This is evidenced by the fact that a very small percentage of members (2.5% in 2007) actively changed superannuation fund and most new fund members ‘defaulted’ into employer-selected funds (Bateman 2009). This may be that they are serious but lack the ability or time to monitor investments in a way required by a sophisticated system. This paper explores the drivers of switching superannuation funds of those working-age Australians. It also analyses the presentation of fund information to the sample population to examine how members use information in their superannuation decisions. This may add insight to the ways fund information is made available and also to the types of members who may need more protection, support or education.
Keywords: Cooper Review; Superannuation; Rational; Informed